2020
DOI: 10.1007/s40279-020-01334-4
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in Competitive Cross-Country Skiers: A Systematic Review and Meta-analysis

Abstract: Introduction In cross-country skiing, the repetitive ventilation of large amounts of cold and dry air strains the airways. The aim of this systematic review was to establish an overview of the current literature on asthma in cross-country skiers, biathletes and ski-orienteers. Methods Six databases were searched on August 29, 2019. The search yielded 2161 articles. Thirty articles fulfilled the search criteria and were pooled together for a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 62 publications
4
30
0
Order By: Relevance
“…Thus, certain signs peculiar to the bronchial mucous membrane inflammatory process in athletes engaged in winter sports were revealed. Similar conclusions were reached by the authors of the research studying the level of macrophages and white blood cells in the material obtained in bronchoalveolar lavage (BAL), which resulted in a significant increase in the number of these cells in healthy athletes after intensive training under low-temperature conditions [31]. During the prospective clinical study, an advanced local inflammatory process in intensively training swimmers was revealed on the background of initially moderately infiltrated bronchial mucous membrane with eosinophils and lymphocytes [32].…”
Section: Peculiarities Of Effort-induced Bronchospasm Pathogenesis In High-school Teenagerssupporting
confidence: 60%
“…Thus, certain signs peculiar to the bronchial mucous membrane inflammatory process in athletes engaged in winter sports were revealed. Similar conclusions were reached by the authors of the research studying the level of macrophages and white blood cells in the material obtained in bronchoalveolar lavage (BAL), which resulted in a significant increase in the number of these cells in healthy athletes after intensive training under low-temperature conditions [31]. During the prospective clinical study, an advanced local inflammatory process in intensively training swimmers was revealed on the background of initially moderately infiltrated bronchial mucous membrane with eosinophils and lymphocytes [32].…”
Section: Peculiarities Of Effort-induced Bronchospasm Pathogenesis In High-school Teenagerssupporting
confidence: 60%
“…asthma, asthma control, cross-country skiing, onset age of asthma, respiratory health cross-country skiers is reported to be found more often as neutrophilic than eosinophilic compared with asthma in the general population, 2 suggesting a difference in the underlying causes of asthma in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of the use of asthma medication in cross-country skiers has varied between 18% and 36% and was approximately 21% in our recent meta-analysis. 2 However, there is lack of knowledge on how the use of asthma medication compares between skiers and nonskiers and whether the typical use of bronchodilators in skiers is on demand for symptoms or pre-emptively before exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to decrease the incidence of cold-induced airway obstructions could play a key role in improving the lung function of athletes, but it is important that any preventive strategy does not interfere with the potential to achieve optimal performance. The prevalence of asthma in cross-country skiers has been estimated at 23%, but may vary depending on the diagnostic criteria used (Mäki-Heikkilä et al 2020). In Sweden, the prevalence of self-reported, physician-diagnosed asthma has been recently reported at 9% (Borna et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of asthma in cross-country skiers has been estimated at 23%, but may vary depending on the diagnostic criteria used (Mäki-Heikkilä et al 2020 ). In Sweden, the prevalence of self-reported, physician-diagnosed asthma has been recently reported at 9% (Borna et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%